Study guides

ββ

Q: What is the solution for y equals -x and 2x-y equals 6?

Write your answer...

Submit

Still have questions?

Related questions

2xy=2*30*2=120

15xy-2xy-7x+x=13xy-6x

2xy substitute 3 for y and 5 for x 2(5)(3) = 30

(x, y) = (-6, 0)

No, it is not.

What is x times 2xy

2xy + 6 = 4xyz Divide through by 2: xy + 3 = 2xyz 3 = 2xyz - xy = y*(2xz - x) Therefore, y = 3/(2xz - x) provided that 2xz - x is not zero.

The solution: x = 6/7 and x = -1

x=14

No because x = 2

x = { +6, -6 }

X squared = x+6 6+x=x squared X=6

People also asked